Pitfalls and potential of institutional change: rain-index insurance and the sustainability of rangeland management - Birgit Müller; Martin Quaas; Karin Frank; Stefan Baumgärtner (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2009)
Rain-index insurance is strongly advocated in many parts of the developing world to help farmers to cope with climatic risk that prevail in (semi-)arid rangelands due to low and highly uncertain rainfall. We present a modeling analysis of how the availability of rain-index insurance affects the sustainability of rangeland management. We show that a rain-index insurance with frequent payoffs, i.e. a high strike level, leads to the choice of less sustainable grazing management than without insurance available. However, a rain-index insurance with a low to medium strike level enhances the farmer's well-being while not impairing the sustainability of rangeland management.
Keywords: D81; G22; Q14; Q56; Q57; 330; Ecological-economic modeling; weather-index insurance; Namibia; grazing management; risk; sustainability; weather-based derivatives